INTEGRATION OF TEXT AND CONTEXT IN ASBĀB AL-NUZŪL: an Analysis of the Scriptural Arguments Used by Terrorism Perpetrators - Muhammad Patri Arifin; Darwis Hude; Muhammad Hariyadi (STAIN Majene, 2026)
This paper examines the important role of asbab al-nuzul in understanding the Qur’an, particularly within the historical context in which the Qur’an was revealed. A qualitative research method with a descriptive–analytical approach is employed to analyze scriptural arguments frequently used by perpetrators of terrorism, namely a series of verses from QS. al-Baqarah (2): 190–193 and QS. al-Ma’idah (5): 44. The study utilizes the concepts of asbab al-nuzul khaṣṣah (specific occasions of revelation) and asbab al-nuzul ‘ammah (general occasions of revelation), as explained by Abu Ishaq al-Syatibi, to interpret and apply these verses. The findings reveal that these scriptural arguments are closely related to specific historical events, such as the Treaty of Hudaybiyyah and disagreements among the Companions regarding the implementation of the stoning (rajm) punishment. Furthermore, the Indonesian context as an independent nation does not correspond with the interpretations advanced by terrorism perpetrators who attempt to justify their actions through these verses. This research, therefore, provides a deeper understanding of asbab al-nuzul and highlights the importance of contextual interpretation to prevent the misuse of Qur’anic verses in acts of terrorism.